Biomechanical characteristics of concussive and sub-concussive impacts in youth sports athletes: A systematic review and meta-analysis - Sundaram, V.; Sundar, V.; Pearce, A. J. (Journal of Sports Sciences, 2023)
This study aimed to quantitatively investigate and report the biomechanical characteristics of concussive and sub-concussive impacts in youth sports. A systematic search was conducted in September 2022 to identify biomechanical impact studies in athletes <18 years of age. Twenty-six studies met the inclusion criteria for quantitative synthesis and analysis. DerSimonian Laird random effects model was used to pool data across the included studies. The pooled estimate of mean peak linear and rotational acceleration of concussive impacts in male youth athletes was 85.56 g (95% CI 69.34-101.79) and 4505.58 rad/s2 (95% CI 2870.28-6140.98), respectively. The pooled estimate of mean peak linear and rotational acceleration of sub-concussive impacts in youth athletes was 22.89 g (95% CI 20.69-25.08) and 1290.13 rad/s2 (95% CI 1050.71-1529.55), respectively. A male vs female analysis in sub-concussive impacts revealed higher linear and rotational acceleration in males and females, respectively. This is the first study to report on impact data in both sexes of youth athletes. Disparity in kinematic impact values suggests future research should aim for standardised measures to reduce heterogeneity in data. Despite this, the data reveals notable impact data that youth athletes are exposed to, suggesting modifications may be required to reduce long-term neurological risks.